UHRF1/DNMT1-MZF1 axis-modulated intragenic site-specific CpGI methylation confers divergent expression and opposing functions of PRSS3 isoforms in lung cancer - Shuye Lin; Hanli Xu; Lin Qin; Mengdi Pang; Ziyu Wang; Meng Gu; Lishu Zhang; Cong Zhao; Xuefeng Hao; Zhiyun Zhang; Weimin Ding; Jianke Ren; et al. (Elsevier, 2023)
As confusion mounts over RNA isoforms involved in phenotypic plasticity, aberrant CpG methylation-mediated disruption of alternative splicing is increasingly recognized as a driver of intratumor heterogeneity (ITH). Protease serine 3 (PRSS3), possessing four splice variants (PRSS3-SVs; PRSS3-V1-V4), is an indispensable trypsin that shows paradoxical effects on cancer development. Here, we found that PRSS3 transcripts and their isoforms were divergently expressed in lung cancer, exhibiting opposing functions and clinical outcomes, namely, oncogenic PRSS3-V1 and PRSS3-V2 versus tumor-suppressive PRSS3-V3, by targeting different downstream genes. We identified an intragenic CpG island (iCpGI) in PRSS3. Hypermethylation of iCpGI was mediated by UHRF1/DNMT1 complex interference with the binding of myeloid zinc finger 1 (MZF1) to regulate PRSS3 transcription. The garlic-derived compound diallyl trisulfide cooperated with 5-aza-2'-deoxycytidine to exert antitumor effects in lung adenocarcinoma cells through site-specific iCpGI demethylation specifically allowing MZF1 to upregulate PRSS3-V3 expression. Epigenetic silencing of PRSS3-V3 via iCpGI methylation (iCpGIm) in BALF and tumor tissues was associated with early clinical progression in patients with lung cancer but not in those with squamous cell carcinoma or inflammatory disease. Thus, UHRF1/DNMT1-MZF1 axis-modulated site-specific iCpGIm regulates divergent expression of PRSS3-SVs, conferring nongenetic functional ITH, with implications for early detection of lung cancer and targeted therapies.